DISEMINASI PENGGUNAAN PUPUK BOKASHI PADA BUDIDAYA PADI SAWAH (Oryza sativa L.) DI KECAMATAN SUKALARANG KABUPATEN SUKABUMI - Meisya Kusumawardani; Achdiyat Achdiyat; Tri Ratna Saridewi (Sekolah Tinggi Pariwisata Mataram, 2020)
Abstract Dissemination is the process of delivering the result of technology to farmers to be known and used. The study aims to determine the level dissemination of bokashi fertilizer application in lowland rice, to analyze the correlation between farmer’s characteristics and external support for dissemination and to determine the strategies to increase dissemination of bokashi fertilizer application. The study lasted for four months, started from March until June 2020 and located in Cimangkok Village, Sukalarang Sub-District of Sukabumi District, West Java Province. Determination of the respondents was using census techniques based on farmer groups at Cimangkok’s village namely Karyamekar and Legok Tani with the total of 40 respondents. Analysis of the data used Descriptive Analysis and Spearman Rank Analysis. Result of the study showed that the level of disseminaton of bokashi fertilizer application at Cimangkok Village was in the low category (70%) before extension and was in the high category (45%) after extension. The factors that have strongest correlation to the dissemination of bokashi fertilizer application are the farmer’s characteristics including farmer’s age and farmer’s education at the level signification (sign<1%) and external support including innovation and media of dissemination at the level signification (sign<1%). The strategies to increase dissemination by extension implemented with providing material about bokashi fertilizer in printed media and shared the online videos. And then the extension is strengthened by making a demonstration plot as an illustration of the material that has been given.